The Relationship Between Stress Management And Academic Boredom and Academic Achievement Of Students Of Boarding School X In Sidoarjo - Khodijatul Jamilah; Ghozali Rusyid Affandi (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study investigates the relationship between stress management, academic boredom, and academic achievement among students at a pesantren (Islamic boarding school) in Sidoarjo. Utilizing a quantitative correlational design, data were gathered from a sample of 200 students. Stress management was measured through coping strategies, while academic boredom was assessed using cognitive, affective, and motivational factors. Contrary to expectations, regression analysis revealed no significant relationship between stress management or academic boredom and academic achievement. These findings suggest that additional factors may play a role in students' academic success within a pesantren context, underscoring the need for further research.